Pengimplementasian Sistem Building Information Modelling Pada Tahapan Penjadwalan Gedung PUT PNJ - Afriani, Budi; Widiasanti, Irika; Wangi, Intan Puspa (Universitas Batanghari Jambi, 2024)
In the process of achieving goals, projects have characteristics called triple constraints, including specific target time, cost, and performance requirements. The delay in the completion process in a project is what will disrupt the triple constraint which has an impact on waste. One of the reasons is that the project still uses conventional methods. This research was conducted to provide information related to conventionally designed scheduling and with the implementation of Building Infortmation Modeling (BIM), namely using several supporting software including, Naviswork, Microsoft Project and Revit at the scheduling stage of multi-storey buildings, namely at the PNJ PUT Laboratory Building. The results showed that the elaboration of scheduling planning using BIM is more efficient, easy to understand, and provides a visualization of the construction sequence and avoids waste. Then, some of the percentage of waste obtained if using conventional methods is, around 10% on materials, 40% of projects are over budget, 30% of projects are reworked, and almost 90% of projects are delayed. Thus, the implementation of BIM in project scheduling is very important to overcome things that can harm a project.